Differences in meiotic recombination rates in childhood acute lymphoblastic leukemia at an MHC class II hotspot close to disease associated haplotypes - Thompson, Pamela (2014)
Childhood Acute Lymphoblastic Leukemia (ALL) is a malignant lymphoid disease of which B-cell precursor- (BCP) and T-cell- (T) ALL are subtypes. The role of alleles encoded by major histocompatibility loci (MHC) have been examined in a number of previous studies and results indicating weak, multi-allele associations between the HLA-DPB1 locus and BCP-ALL suggested a role for immunosusceptibility and possibly infection. Two independent SNP association studies of ALL identified loci approximately 37 kb from one another and flanking a strong meiotic recombination hotspot (DNA3), adjacent to HLA-DOA and centromeric of HLA-DPB1. To determine the relationship between this observation and HLA-DPB1 associations, we constructed high density SNP haplotypes of the 316 kb region from HLA-DMB to COL11A2 in childhood ALL and controls using a UK GWAS data subset and the software PHASE. Of four haplotype blocks identified, predicted haplotypes in Block 1 (centromeric of DNA3) differed significantly between BCP-ALL and controls (P = 0.002) and in Block 4 (including HLA-DPB1) between T-ALL and controls (P = 0.049). Of specific common (>5%) haplotypes in Block 1, two were less frequent in BCP-ALL, and in Block 4 a single haplotype was more frequent in T-ALL, compared to controls. Unexpectedly, we also observed apparent differences in ancestral meiotic recombination rates at DNA3, with BCP-ALL showing increased and T-ALL decreased levels compared to controls. In silico analysis using LDsplit sotware indicated that recombination rates at DNA3 are influenced by flanking loci, including SNPs identified in childhood ALL association studies. The observed differences in rates of meiotic recombination at this hotspot, and potentially others, may be a characteristic of childhood leukemia and contribute to disease susceptibility, alternatively they may reflect interactions between ALL-associated haplotypes in this region.